The impact of a negative labor demand shock on fertility: Evidence from the fall of the Berlin Wall - Hannah Liepmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
How does a negative labor demand shock impact individual-level fertility? I analyze this question in the context of the East German fertility decline after the fall of the Berlin Wall in 1989. Exploiting di erential pressure for restructuring across industries, I nd that throughout the 1990s, women more severely impacted by the demand shock had more children on average than their counterparts who were less severely impacted. I argue that in uncertain economic circumstances, women with relatively more favorable labor market outcomes postpone childbearing in order not to put their labor market situations at further risk. This mechanism is relevant for all quali cation groups, including high-skilled women. There is some evidence for an impact on completed fertility.
Keywords: J13; J23; P36; 330; Fertility; Labor Demand Shock; Industrial Restructuring; East Germany